Impact of Heating Exposure on the Micro-Push-Out Bond Strength of Bioceramic Sealers - Guilherme Rodrigues Cândido Lopes; Maria Eduarda Paz Dotto; Lincon Hideo Nomura; Daniela Peressoni Vieira Schuldt; Lucas da Fonseca Roberti Garcia; Cleonice da Silveira Teixeira (Hindawi Limited, 2023)
Introduction. The aim of this study was to evaluate the effect of heating of bioceramic and epoxy resin-based sealers on their micro-push-out bond strength (BS) to root canal dentin. Methods. After criterial selection, 30 human teeth were decoronated and 1-mm thick slices (n = 60) were obtained perpendicularly along tooth axis, from cervical and middle root thirds, with a diamond disc attached to a cutting machine. In each slice, three 1.0-mm diameter orifices were made. After rinsing with 17% EDTA and 2.5% NaOCl, each orifice was filled with Bio-C Sealer or BioRoot RCS or AH Plus, according to the manufacturers' instructions. After filling, half of the slices (n = 30) were heated at 100°C for 1 min, and the other half were kept at room temperature. After 7 days-controlled storage, micro-push-out test was performed in a Universal Testing Machine. Failures were analyzed using a stereomicroscope. Statistical analysis was performed with One-Way ANOVA and post hoc Tukey (α = 5%) tests. Results. AH Plus demonstrated higher BS values after heating (p=0.001) when compared to nonheated. The other sealers did not show a statistically significant difference (p>0.05). When heated, the average BS values for AH Plus were higher than for BioRoot RCS and Bio-C Sealer (p<0.001). Cohesive failure mode was the most frequent, followed by adhesive and mixed ones. Conclusion. Heating provided a higher push-out BS to root dentin for AH Plus and did not influence BioRoot RCS or Bio-C sealer.